2007
DOI: 10.1007/s11027-007-9115-4
|View full text |Cite
|
Sign up to set email alerts
|

The value of energy efficiency programs for US residential and commercial buildings in a warmer world

Abstract: Buildings, Climate change scenarios, Economic benefits, Energy efficiency, Energy modeling, Mitigation, Residential and commercial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In our findings, the commercial and industrial sectors are the dominant drivers of energy demand increases. By considering a broader range of energy-using sectors, we highlight the potentially important impacts of commercial and industrial adaptation to climate change, which has only been explored for specific regions 4,3538 by few studies that confirm the potentially large impacts of these sectors.…”
Section: Discussionmentioning
confidence: 99%
“…In our findings, the commercial and industrial sectors are the dominant drivers of energy demand increases. By considering a broader range of energy-using sectors, we highlight the potentially important impacts of commercial and industrial adaptation to climate change, which has only been explored for specific regions 4,3538 by few studies that confirm the potentially large impacts of these sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Engineering studies in temperate developed countries have found that the total amount of energy consumption for space conditioning decreases slightly with warming because the additional energy for cooling is offset by the reduction in energy for heating (Rosenthal et al, 1995;Scott et al, 2008). Nonetheless, economic studies reveal that expenditures on energy rise with temperature (Morrison and Mendelsohn, 1999;Mendelsohn, 2001;Mansur et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, HDD were projected to decrease, while CDD were expected to grow by the late century, both countrywide 5 7 18 20 21 22 23 24 25 and worldwide 17 24 26 27 28 , albeit the rate and magnitude of change in each parameter differed with the study. Secondly, changes in national residential net use of delivered energy were anticipated to result in modest savings 5 20 21 22 26 , because the reduction in heating fuels was expected to more than offset the rise in electricity demand for air conditioning 5 . However, on a regional level, combined energy demand was forecasted to exhibit spatial heterogeneity 20 : In northern areas with more than 4,000 HDD, the combined degree-day index dropped substantially, as compared to the areas in the South, where a reverse climatic effect was anticipated 5 .…”
mentioning
confidence: 97%